1978
DOI: 10.1002/jmor.1051570303
|View full text |Cite
|
Sign up to set email alerts
|

Re‐regeneration of lower jaws and the dental lamina in adult urodeles

Abstract: Transverse amputations were carried out through one-third fully regenerated jaw segments and through normal tissue of the mandible on the same and opposite sides of the jaw in adults of Notophthalmus viridescens. Collectively the results suggest that, in adult urodeles, the mandible and the dental lamina can be replaced in an identical manner more than one time. Although the major histological events are the same in jaw regeneration and re-regeneration, regrowth is more rapid in re-regeneration. It appears tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
2
12
0
1
Order By: Relevance
“…Previous reports have shown that, despite their development as directly differentiating intramembranous bones, the jawbones of newts regenerate through a cartilage intermediate (Graver, 1978;Ghosh et al, 1994). We therefore tested whether a similar process occurs in zebrafish.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that, despite their development as directly differentiating intramembranous bones, the jawbones of newts regenerate through a cartilage intermediate (Graver, 1978;Ghosh et al, 1994). We therefore tested whether a similar process occurs in zebrafish.…”
Section: Resultsmentioning
confidence: 99%
“…Although large bone lesions often fail to repair in mammals, many reptiles, amphibians and fishes can regenerate entire appendicular, tail and jaw skeletons (Goss and Stagg, 1958;Graver, 1978;Ghosh et al, 1994;Brockes, 1997;Iovine, 2007). A commonality between large-scale bone regeneration in these species and fracture healing in humans is the formation of a cartilage callus that bridges the wound, in particular when the fracture is not mechanically stabilized (Pritchard and Ruzicka, 1950;Lieberman and Friedlaender, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The complete amputation of the dental lamina of the vomer or of the palatine gives rise to toothless bones (Clemen, 1979 b ). Experiments dealing with repeated regeneration of the jaw have shown that the events, especially those involved in the repeated regeneration of the dental lamina, are the same as in normal regeneration but that the regrowth is more rapid (Graver, 1978).…”
Section: Tooth Regenerationmentioning
confidence: 99%
“…In amphibia, although regenerating teeth are said to be added in an alternating sequence in the lower jaws of adult Notophthalmus viridescens (Graver, 1978), the few investigations on early lower dentition development, e.g. in Hypogeophis rostr.…”
Section: Den Tit Ionmentioning
confidence: 99%